Penurunan TSS, COD, dan Total-Nitrogen pada Air Lindi dengan Metode Constructed Wetland Tanaman Typha Angustifolia - Thineza Ardea Pramesti; Mohamad Mirwan (Yayasan Literasi Sains Indonesia, 2023)
Landfill is a place to dispose of waste. There are still many landfills in Indonesia that use open dumping. Klotok Landfill in Kediri City uses a sanitary landfill where if you use the sanitary landfill method, leachate can be accommodated in a shelter. Leachate comes from waste decomposition. One of the leachate treatments is constructed wetlands. Constructed wetlands are treatment with a design that copy the natural system of plants to treat wastewater by involving several process mechanisms such as physics, chemistry, and biology. In this study, Typha angustifolia were used because these plants were considered capable of processing leachate. Using subsurface flow and continuous process is expected to reduce TSS, COD, and Total-Nitrogen. Sampling time was carried out in the 6th, 8th, 10th, and 12th, and 14th days. The results of TSS, COD, and Total-Nitrogen obtained were highest at 5L/day discharge with the 14th day sampling reaching 96.30%, 90%, and 89.16%. The average temperature and pH results obtained reached 26.92 ℃ and 7.9. The temperature and pH in this study are still within the optimal range for constructed wetland processing methods.